DESAIN PEKERJAAN DAN ASSIGNMENT PROBLEM DALAM PENGELOLAAN KARYAWAN - Muhammad Isa (Institut Agama Islam Negeri Padngsidimpuan, 2015)
Abstract It’s very important for a business organization to prepare the best job design. It will help us to get the highest performance. Job enlargment, job enrichment, and job characteristics redesign are parts of it. Manager must decide what, who, where, when, and how to do the job. Hungarian technique is a solution for assignment problem to get minimum cost or maximum profit. Hungarian technique introduced by D. Konig from Hungaria. Keywords: Design, Job Assignment, Cost.